The Evolution of Uzbekistan’s Legal System: A Historical Perspective - Jasurbek, Asadullaev (Researchparks Publishing, 2024)
This article presents the contemporary and historical legal system of Uzbekistan, aiming to explore the nation’s legal evolution, understand its structure, and identify modern legal reforms. The narrative delves into significant periods in Uzbekistan’s legal history, particularly the ancient legal traditions woven through the centuries, the cultural and economic changes shaping legal norms, and the transformative legal landscape during pivotal epochs. The article aims to provide readers with a comprehensive overview of Uzbekistan’s legal journey, capturing the complexities and adaptations of its legal framework over time.